Getting them through the door: Social and behavioral determinants of uptake and engagement in an obesity intervention. Issue 1 (January 2023) - Rodriguez, Alina; Korzeniowska, Katarzyna; Szarejko, Kamila; Borowski, Hubert; Brzeziński, Michał; Myśliwiec, Małgorzata; Czupryniak, Leszek; Berggren, Per-Olof; Radziwiłł, Marcin; Soszyński, Piotr
Abstract: Using data from a large-scale screening program (N = 19634), we aimed to prospectively identify factors predicting uptake (i.e. acceptance of the invitation) and engagement (i.e. participation in at least two sessions) in a multi-component-intensive-behavioral-intervention for obesity-management (MBIOM) intervention targeting adolescents (n = 2862; 12–14 years; BMI ≥90th percentile). Approximately one third of adolescents most in need of weight management declined the initial invitation to enter the MBIOM. Poor diet, sedentary behavior, and parental education predicted willingness to enter and stay in the intervention, however measured body mass index did not matter. Perceived family support, instead of initial motivation, facilitated engagement. Our results provide new insights on the importance of regional socio-geographical factors including trust in local authorities. Highlights: Determinants of uptake of obesity management interventions are unknown due to non-participation. 34 % of adolescents with morbid obesity declined uptake in this obesity management intervention. Neither measured body mass index (BMI) nor readiness for change impacted uptake or engagement. Living in a region of trust in local authorities was related to uptake. Poor diet and low physical activity were determinants of uptake and engagement.